IMPLEMENTATION OF COVID-19 DIRECT CASH ASSISTANCE (BLT) IN SERDANG BEDAGAI DISTRICT - Zainuddin Nasution; Anwar Soleh Purba; Saiful Ahyar Purba (Universitas Pahlawan Tuanku Tambusai, 2023)
It is important to know what the problems are in implementing the Covid-19 BLT Implementation. Because we can use the problems that occur as a strategy if almost the same problem reappears. The data collection method used in this research is qualitative. Collecting data in this study used the implementation model theory of Marilee S. Grindle. There are several variables in the process of determining success in implementation, including interests involved, types of benefits, degree of change involved, location of decision-making, program implementers, and resources involved. The results of the discussion and research that has been carried out, the results obtained are the Implementation of Direct Cash Assistance Covid - 19 in Serdang Bedagai Regency. Based on the discussion at the beginning, it can be concluded that the Covid-19 BLT in Pematang Pelintahan Village in 2020 is determined by several aspects, namely: Interests Affected, where many families have not received assistance at all. Type of Benefit, using BLT money will not necessarily be prosperous because the money you get is only enough for your daily needs. Desired Degree of Change, where the village office has the wrong target in registering people who are eligible for assistance. Location of Decision Making, where the accuracy of the target starts right because it goes through processes and procedures. Program Executors, by the education they have Bachelor's degrees so their ability to identify and solve problems quickly. Resources Involved, there are facilities and infrastructure support in the form of buildings, motorbikes, tables, chairs, and office stationery.